'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Femmes; Université McGill

The First Leaders of McGill's School of Architecture: Stewart Henbest Capper, Percy Nobbs, and Ramsay Traquair - Gournay, Isabelle (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

George Heath MacDonald (Class of 1911): The Story of One Graduate from McGill University's School of Architecture - Johnson, Percy (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

Teaching the History of Architecture at McGill, 1896-1903 - Schoenauer, Norbert (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

Montréal... l'histoire oubliée (Histoire Québec, 1996)
Number: 1
Keywords: Arts sacrés; Leduc; Ozias; Musées; Peinture; Églises

Le patrimoine du Collège de Montréal: le cas de l'Ermitage - Attab, Ahmed (Université de Montréal, 1996)
Keywords: Collège de Montréal; Communautés religieuses; Patrimoine; Sulpiciens

Le processus d'élaboration d'un projet d'architecture: le cas de l'agrandissement du Musée des beaux-arts de Montréal - Bendeddouch, Assya (Université de Montréal, 1996)
Keywords: Musée des Beaux-Arts; Musées

L'évolution de la rue Sainte-Marie / Notre-Dame entre 1871 et 1911, dans les limites du quartier Saint-Jacques - Berthelon, Stéphanie (Université de Savoie (Chambéry-Annecy), 1996)
PAGES INTROUVABLE
Keywords: Quartiers; Rues; Saint-Jacques

Un type de maison ouvrière: le déclin de la maison de fond de cour à Montréal, 1880-1920 - Carey, Luc (Université du Québec à Montréal, 1996)
Keywords: Logement

Montréal et les maisons de type Wartime - Cayla, Jean-Claude (Continuité, 1996)
issued: 1996-24-00
Keywords: Logement

Northern deco: Art deco architecture in Montreal - Cohen-Rose, Sandra (Corona, 1996)

Habitat et économie domestique en milieu ouvrier: la rue de Montcalm à Montréal, 1871-1901 - Comte, Fabrice (Université Lumière Lyon 2, 1996)
Keywords: Rues

La modernité et ses acquis: le Jardin botanique de Montréal - Des Rochers, Jacques (Cap-aux-Diamants, 1996)
issued: 1996-22-00
Keywords: Jardin botanique

Coming into Site: Identity, Community and the Production of Gay Space in Montréal - Doyle, Vincent André (Université McGill, 1996)

L'espace social de Montréal, 1951-1991 - Drouilly, Pierre (Septentrion, 1996)

Le bain Généreux: reflet d'un quartier - Écomusée du fier monde (Écomusée du fier monde, 1996)
Keywords: Centre-sud (quartier); Quartiers

Les gratte-ciel des temps modernes: l’attrait de la démesure - Forget, Madeleine (Continuité, 1996)
issued: 1996-23-00
Keywords: Gratte-ciel

Les Resther, entrepreneurs et architectes de la région de Montréal, 1820-1911 - Gagnon, Julie Élizabeth (Université du Québec à Montréal, 1996)

Représenter l'Holocauste: le traitement et la représentation de l'Holocauste dans les musées-mémoriaux d'Amérique du Nord: étude comparative – le United States Holocaust Memorial Museum et le Centre commémoratif de l'Holocauste à Montréal - Gauvin, Nicolas A. (Université Concordia, 1996)
Keywords: Juifs; Musées

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Gardenvale: une cité-jardin des années 20 - Girard, Jean-Pierre (Continuité, 1996)
issued: 1996-24-00

La fonction résidentielle dans le centre-ville de Montréal - Hampson, Ken (Université de Montréal, 1996)
Keywords: Centre-ville; Logement; Quartiers

Analyse des structures et des technologies de construction des dômes à Montréal - Jakimova, Snejanka (Université de Montréal, 1996)

Reconversion économique, développement local et mobilisation sociale: le cas de Montréal - Klein, Juan-Luis; Waaub, Jean-Philippe (Recherches sociographiques, 1996)
Number: 3
Keywords: Quartiers; Rosemont; Saint-Laurent (ville)

Une réflexion sur la revitalisation du Vieux-Montréal: le rôle des intervenants - Kraba, Mohamed Amine (Université de Montréal, 1996)
Keywords: Quartiers; Vieux-Montréal

Montréal à l’heure des bains - Labonne, Paul (Continuité, 1996)
issued: 1996-22-00

Modélisation tridimensionnelle régionale et locale de l'écoulement de l'eau souterraine sur l'île de Montréal et au Centre de Tri et d'Élimination des Déchets de la ville de Montréal - Lepage, Nicolas (Institut national de la recherche scientifique - Géoressources, 1996)
Keywords: Égouts

L’édifice de la Sun Life: un prestige renouvelé - Marchand, Denys (Continuité, 1996)
issued: 1996-23-00
Keywords: Banques; Gratte-ciel

Ethnographie d'une pratique ludique urbaine: le skateboard sur la place Vauquelin à Montréal - Pégard, Olivier (Université de Montréal, 1996)
Keywords: Places publiques

Inventaire du patrimoine moderne à Montréal [Résidence des frères Jarry; Habitations Canada Cement; Pavillon-restaurant du Lac aux Castors; Église Notre-Dame-du-Bel-Amour; Supermarché Steinberg, magasin no. 67; Immeuble à appartement Embassy Row; Station de métro Peel; Caisse populaire Saint-Zotique] - Picard, Michèle; Besner, Guy (ARQ - Architecture Québec, 1996)
Keywords: Patrimoine

Situation du patrimoine moderne à Montréal - Picard, Michèle; Besner, Guy (ARQ - Architecture Québec, 1996)
Keywords: Patrimoine

Le paysage toponymique dans la région de Montréal du XIXe siècle à nos jours - Pollet Villard (Université Laval, 1996)
Keywords: Toponymie

L'église Sainte-Marguerite-Marie-Alacoque, une oeuvre d'Ernest Cormier - Racine, Paul (Histoire Québec, 1996)
Number: 1
Keywords: Cormier; Ernest; Sainte-Marguerite-Marie / Sainte-Marguerite-Marie-Alacoque (paroisse); Églises

Privacy in Row Houses of Montreal - Rahbar, Mehrdad (Université McGill, 1996)
Keywords: Logement

Fer et fins décors: l’ornement métallique à Montréal - Rémillard, François (Continuité, 1996)
issued: 1996-23-00

Analyse de la valeur patrimoniale de l'église St. James United à Montréal - Spiridon, Mirela (Université de Montréal, 1996)
Keywords: Patrimoine; Églises

Cathédrale Marie-Reine-du-Monde: analyse de l'évolution historique et architecturale - Ursu, Daniela (Université de Montréal, 1996)
Keywords: Cathédrale

"Advancing the Material Interests of the Redeemer's Kingdom": The Erskine Presbyterian Church, Montreal, 1894 - Zubalik, Janis R. (Université Concordia, 1996)
Keywords: Erskine (église); Églises